Analisis Kemampuan Menulis Permulaan Siswa Kelas 1 Sekolah Dasar - Mila Hanifa; Chandra Chandra; Salmaini Safitri Syam (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to analyze the initial writing skills of grade 1 Elementary School students. Initial writing is the initial stage for students in recognizing letter shapes, composing syllables, and being able to write simple words and sentences. The method used in this study is descriptive qualitative with observation and documentation techniques. The results of the analysis show that the writing skills of grade 1 students vary greatly, influenced by fine motor readiness, the learning environment, and the role of teachers in providing appropriate exercises. Most students still have difficulty in writing letters with the correct and neat shape. Therefore, an interesting and repetitive learning strategy is needed so that students can improve their writing skills gradually.